Course on tunnel design and construction 25-27 June 2001 Royal Holloway, University of London (Thomas Telford, 2001)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a course held at University of London in June 2001.